Travessias de Cecília: a caminho da educação matemática no CEEJA Padre Moretti - Rondônia - Cordeiro, Edna Maria [UNESP] (2014)
Initially, this research intended only realize the scenario of Mathematics Education in the Centro Estadual de Educação de Jovens e Adultos (CEEJA) Padre Moretti, the historical path from 1977 to 2012, but the go thru the perspective of the New Cultural History as thought by Chartier (1990), the survey was expanded from data obtained on the performance of that center, the story of Rondônia and the family of Cecilia character of this text. Consequently, were also discussed formative processes of character and other teachers in Rondônia. The data emerging from the creation of documents such as laws, resolutions and ordinances (legal framework) referencing EJA courses in Rondônia; designs found in the archives of CEEJA; located in old newspapers library Francisco Meirelles, and memories of Cecilia and ten respondents (graduates and professors). Interpretations we had from the collected data gave rise to the polyphonic text and dialogical perspective of Bakhtin (2011). The concept of culture, from Geertz (2008) enabled the construction of history, that is, Cecilia crossings in search of an understanding about the plot of this text that moves between difficulties and opportunities of characters text and Education in the state of Rondônia. With regard to history of Rondônia, was perceived diversity of opportunities work up and the population of financial improvements, however were always present many difficulties, such as lack of infrastructure, education and health, and political performances uncommitted to the general population. In the history of Education Youth and Adults (EJA) in Rondônia and CEEJA moments were identified oscillations between extending the decline in attendance and performances and the number of students of the institution. When analyzing the data on Mathematics, the most frequently observed difficulties in the learning process were: lack of prior knowledge of students to accompany a curriculum geared toward...